Fast fractal prediction of surge over underwater vehicle. (16th February 2016) - Tang, Zhijie; Luo, Qian; Liu, Pinglong; Luo, Jun; Xie, Shaorong; Leng, Xinnan; Li, Tianlun
Abstract : In order to realize accurate control of underwater vehicles, this paper proposed a fractal prediction model of surge. Firstly, we introduce the current state-of-the-art of fractal prediction; secondly, we complete a fractal analysis with the R_S method, calculating the fractal dimension of surge using the short-time dimension method; thirdly, we correct the vertical scaling factor of the Iterated Function System (IFS) using the fractal dimension. Then the predictive value can be calculated through anti-iteration according to the statistical significantly IFS and proposing a fractal prediction model. Finally, we complete a simulation analysis based on the actual data and a comparison to another prediction algorithm. The result shows that the fractal prediction algorithm of this article has better comprehensive performance. Graphical Abstract: